Pendekatan Partisipatif Dalam Edukasi Anti-Bullying Di Sekolah Dasar: Studi Kasus Di Sdn 01 Balai Panjang - Dyan Sukma Erita; Elisa Yulianti Fadla; Fadiyatul Khaira; Ghaisa Zahira Syifa; Yofika Larassanda; Hambali Hambali (CV. ITTC INDONESIA, 2026)
Bullying remains a problem in elementary schools in Indonesia. This study examines the effectiveness of a participatory approach in an anti-bullying education program implemented by the Community Service Program (KKN) team from Padang State University at SDN 01 Balai Panjang, Balai Panjang Village, Lareh Sago Halaban District, Lima Puluh Kota Regency, West Sumatra, on January 22, 2026. The combination of five approaches—interactive lectures, Smart Board media, anti-bullying chants, written reflection sessions, and question-and-answer/discussion sessions—successfully improved students' understanding of the definition, types, and impacts of bullying. This participatory method also improved students' ability to resist and report bullying, as well as their empathy for fellow students. The program's success stemmed from the support of Smart Board technology, student participation, and school support. Factors that hindered this activity included time constraints and the reluctance of some students to share their experiences verbally. The study's findings emphasize the effectiveness of interactive methods compared to one-way lectures in creating a safe and inclusive learning environment.